Fatigue analysis of computer‐aided design/computer‐aided manufacturing resin‐based composite vs. lithium disilicate glass‐ceramic. (20th May 2016) - Ankyu, Shuhei; Nakamura, Keisuke; Harada, Akio; Hong, Guang; Kanno, Taro; Niwano, Yoshimi; Örtengren, Ulf; Egusa, Hiroshi
Abstract : Resin‐based composite molar crowns made by computer‐aided design/computer‐aided manufacturing (CAD/CAM) systems have been proposed as an inexpensive alternative to metal‐ceramic or all‐ceramic crowns. However, there is a lack of scientific information regarding fatigue resistance. This study aimed to analyze the fatigue behavior of CAD/CAM resin‐based composite compared with lithium disilicate glass‐ceramic. One‐hundred and sixty bar‐shaped specimens were fabricated using resin‐based composite blocks [Lava Ultimate (LU); 3M/ESPE] and lithium disilicate glass‐ceramic [IPS e.max press (EMP); Ivoclar/Vivadent]. The specimens were divided into four groups: no treatment (NT); thermal cycling (TC); mechanical cycling (MC); and thermal cycling followed by mechanical cycling (TCMC). Thermal cycling was performed by alternate immersion in water baths of 5°C and 55°C for 5 × 10 4 cycles. Mechanical cycling was performed in a three‐point bending test, with a maximum load of 40 N, for 1.2 × 10 6 cycles. In addition, LU and EMP molar crowns were fabricated and subjected to fatigue treatments followed by load‐to‐failure testing. The flexural strength of LU was not severely reduced by the fatigue treatments. The fatigue treatments did not significantly affect the fracture resistance of LU molar crowns. The results demonstrate the potential of clinical application of CAD/CAM‐generated resin‐based composite molar crowns in terms of fatigue resistance.